The mRNA expression of DRD2, PI3KCB, and AKT1 in the blood of acute schizophrenia patients. (30th September 2016) - Liu, Liang; Luo, Yin; Zhang, Guofu; Jin, Chunhui; Zhou, Zhenhe; Cheng, Zaohuo; Yuan, Guozhen
Abstract: The phosphoinositide 3 kinase - protein kinase B (PI3K-Akt) signaling pathway plays an important role in the dopamine D2 receptor (DRD2) pathway and in the pathophysiology of schizophrenia. This study measured the mRNA levels of DRD2, PI3KCB, and AKT1 in peripheral blood samples from 24 acute schizophrenia patients and 20 healthy controls using real-time quantitative reverse transcription polymerase chain reaction (real-time qRT-PCR). We found that in the acute schizophrenia patients, the mRNA expression levels of DRD2 and PI3KCB were significantly lower than those in the healthy controls, while the AKT1 mRNA levels were significantly higher than those in the healthy controls. A significant relationship between the mRNA levels of DRD2 and PI3KCB was found only in the controls. In conclusion, the gene expression state of the DRD2-PI3K-AKT signaling cascade differed significantly between acute schizophrenia patients and healthy controls. Highlights: DRD2 and PI3KCB mRNA levels were lower in acute SZ patients than those in controls. AKT1 mRNA levels were higher in acute SZ patients than those in controls. DRD2 and PI3KCB mRNA levels have corelation in controls, not in acute SZ patients.